ANTESEDEN DARI EMPLOYEES’ ENGAGEMENT: SEBUAH MODEL MODERATED MEDIATION DARI PERCEIVED ALTERNATIVE JOB OPPORTUNITIES, EMPLOYEES’ ATTITUDE DAN EMPLOYEES’ MOTIVATION DOSEN DI UNIVERSITAS “X” [THE ANTECEDENTS OF EMPLOYEES’ ENGAGEMENT: A MODERATED MEDIATION MODEL OF LECTURER’S PERCEIVED ALTERNATIVE JOB OPPORTUNITIES, EMPLOYEES’ ATTITUDE AND EMPLOYEES’ MOTIVATION AT “X” UNIVERSITY ] - Indrawan, Indrawan (Universitas Pelita Harapan, 2023)
Abstract This study aims to investigate the role and potential of mediating and moderating variables which are the antecedents for Employees' Engagement (EE) at University “X” by developing and testing an empirically integrated model to study the mediating role of Employees' Attitude (EA) and Employees' Motivation (EM) on the relationship between Transformational Leadership (TL) and EE being moderated by Perceived Alternative Job Opportunities (PAJO). This study uses a quantitative research approach with survey research methods (non-experimental). The data collection method was carried out through an E-questionnaire for 98 lecturers at the